Asset Management and Third-Party Funds on Firm Value with Profitability as an Intermediate Variable in the Financial Industry on the Indonesia Stock Exchange - Herlina Rasjid; Harun Blongkod (Jurnal Manajemen Industri dan Logistik, 2024)
Research is a type of qualitative research with a descriptive approach to test asset management and third-party funds against company value with profitability as an intermediate variable in the Financial Industry listed on the Indonesia Stock Exchange for the period 2017-2021. With a population of 49 banks listed on the IDX and a sample used as many as 26 banks with a total observation of 130 units according to the purposive sampling method with sampling criteria, namely the company did not experience losses for five consecutive years or during the study period. The results of the analysis show that directly the management of assets and third-party funds has a significant effect on profitability. For indirect influences, profitability cannot mediate asset management against company value, while profitability is able to mediate third-party funds against company value in the financial industry on the Indonesia Stock Exchange.